Emotions and involvement of foster carers preparing to welcome children arriving from war zones. (18th October 2021) - Euillet, Séverine; Hilbold, Mej; Ganne, Claire; Faisca, Elodie; Turlais, Amélie
Abstract: In France, the fosterage of children arriving from war zones is rather marginal and does require the consideration of two major issues: emotions and commitment, both at stake among the foster carers. These issues can be apprehended through the way in which professionals conceive their work, their relationship with the child, but also the singular and specific nature of these children's situation. We, therefore, conducted a qualitative study in the field of Educational Sciences using semi‐structured interviews to gather the experience of 11 foster carers preparing to welcome French children coming from war zones. The analysis of their discourses shows that this exceptional situation reinforces their involvement and their emotional bond. The time devoted to the preparation of the child's reception is precious as it gives meaning to the work, arouses ambivalent emotions and builds an imaginary child.